Cobalt-phthalocyanine-modified two-dimensional cobalt hydroxide complexes for highly selective electrocatalytic reduction of CO2 to CO. Issue 3 (6th January 2023) - Sun, Zhaoyang; Zhai, Yanling; Zheng, Lirong; Guo, Weiwei; Dong, Weiwei; Fang, Zijian; Jiao, Lei; Zhu, Zhijun; Lu, Xiaoquan; Tang, Jianguo
Abstract : We have synthesized CoPc/α-Co(OH)2 catalysts for CO2 electroreduction to CO with a faradaic efficiency of 98.4%. The excellent catalytic performance could be mainly attributed to the strong interaction between CoPc molecules and α-Co(OH)2 support. Abstract : Cobalt phthalocyanine (CoPc)-modified two-dimensional alpha-cobalt hydroxide (α-Co(OH)2 ) catalysts exhibited excellent electrochemical performance for the reduction of CO2 to CO. The faradaic efficiency (FE) and current density reached 98.4% and 22.4 mA cm −2, respectively. Due to the strong interaction between the metal active sites and the support, the 4.1%-CoPc/α-Co(OH)2 complex displayed a favorable electron density configuration, efficient charge transfer and a large electrochemical surface area.